Pyramidal Ownership and SOE Innovation - Wang, Joyce C.; Yi, Jingtao; Zhang, Xiuping; Peng, Mike W. (Journal of Management Studies, 2022)
AbstractHow can state‐owned enterprises (SOEs) become more innovative in emerging economies where market competition emerges and state socialism remains? Rooted in a state socialism logic that traditionally prioritizes central planning, SOEs are increasingly challenged by a market competition logic espousing efficiency and innovation. We posit that the challenge, stemming from the grip of the state as the ultimate owner, may be mitigated for some SOEs under pyramidal ownership. A pyramid features SOEs being organized into chains of firms, creating indirect ownership and control through pyramidal layers. Such layers insulate state intervention in lower‐tier SOEs, loosening the grip of the state socialism logic and facilitating corresponding SOEs’ acceptance of the market competition logic, as reflected in more innovation. Leveraging a sample of SOEs in China, we find that SOEs innovate more when the number of pyramidal layers between them and the state increases. In addition, the innovation‐facilitating role of pyramidal ownership hinges on industry regulations and institutional development. Overall, this paper integrates research on institutional logics and pyramidal ownership to deepen our understanding of SOE innovation.